Design Expert System for Auditing Financial Accounts - Khalid Al-Bakoaa, Abdul Rahman; Hasoon, Safwan O. (Technium Business and Management, 2022)
This paper presents an account audition system based on (Expert System), an artificial intelligence technique. This paper presents an account audition system based on (Expert System), an artificial intelligence technique. Since the limited studies dealt with using artificial intelligence in a general and expert system in auditing accounts in Iraq (within the researcher’s knowledge limits), the researcher tried to tackle these two subjects in his current study to apply them in reality. The expert system that is designed within rules and facts of knowledge base analyzes, audits, and extracts data from financial tables within accounting distributions consist included such as names of accounts and their numbers whose values are represented within cost centers represented by certain symbolic numbers that differ from one institution to another and obtaining the required results by using an applicable knowledge base. The Proposed system approach offers a practical method of auditing and distributing the required data by using the expert systems manually by many auditors. Using the expert system led to lessening time and effort taken to make audits and the accuracy of obtaining results.